The microstructure, physical and mechanical properties of silicon carbide with alumina and yttria as sintering additives - Johari, M.I.A. (Asian Research Publishing Network, 2016)
Silicon carbide has gain much attention in recent years as the best material for the application in harsh environment condition. This is due to their excellent properties such as good wear resistance with high hardness and strength at elevated temperature. In this study, the sintered specimen of silicon carbide with sintering additives of four different compositions were fabricated using powder metallurgy method. Physical properties were measured by means of bulk density and apparent porosity whereas the mechanical property was measured in term of hardness. From this study, it can be observed that the silicon carbide was sintered to about 0.93 of its relative density by using alumina and yttria as sintering additives. This finding was as a result of a eutectic liquid formed between alumina and yttria at sintering temperature of 1930Â°C. The specimen with 25 wt. of sintering additives gave the maximum value of hardness of 2601 HV. Â© 2006-2016 Asian Research Publishing Network (ARPN).